The Effect Of Work Stress And Work Ethic On Employee Performance By Providing Incentives As An Intervening Variable In The Public Works And Spatial Planning Office Of Asahan Regency - Shandy Evanda Santayana; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
Work stress and work ethic are important factors that affect employee performance, especially in a competitive work environment. This study aims to find out and analyze the influence of work stress and work ethic on employee performance with incentives as an intervening variable in the Public Works and Spatial Planning Office of Asahan Regency. The research uses a causal associative quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The sample used was 145 employees with a saturated sample technique. The results showed that work stress had a negative influence on employee performance, with a T-statistical value of 1.027 < 1.96 and a P-value of 0.306 > 0.05. On the contrary, work ethic has a positive and significant influence on employee performance, with a T-statistical value of 3.371 > 1.96 and a P-value of 0.001 < 0.05. Incentives have also proven to have a significant effect on employee performance, with a T-statistical value of 12.108 > 1.96 and a P-value of 0.000 < 0.05. However, incentives were unable to mediate the effect between work stress and employee performance, as shown by the T-statistical value of 1.692 < 1.96 and the P-value of 0.093 > 0.05. On the contrary, incentives were able to mediate the influence of work ethic on employee performance significantly, with a T-statistical value of 11.565 > 1.96 and a P-value of 0.000 < 0.05. These results provide insight that the right incentive management strategy can strengthen the positive influence of work ethic on employee performance, while work stress management needs to be optimized to minimize its negative impact on performance.